ALAT PENGUMPUL BRONDOLAN BUAH UNTUK MENINGKATKAN PENDAPATAN PETANI KELAPA SAWIT - Indah Rizkya Tarigan; Khalida Syahputri; Dwi Endah Widyastuti (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
Oil palm plantations are highly developed in Indonesia Especially North Sumatra. In the process of oil palm harvest, will produce palm kernels that fall to the ground. the oil palm seed is a mature palm fruit and can be sold. Based on preliminary observations with partners, they have difficulty in collecting fallen palm kernel. So many of the seeds of palm oil are abandoned and not sold. Farmers' income is reduced due to wasted crops. The absence of work facilities that occupy and the exhaustion of workers is the cause of farmers do not collect the seeds of palm. The activity of collecting palm kernel seeds is still done manually. The use of farming tools to collect palm kernel seeds facilitates the collecting of fallen palm kernel, so that the harvesting activities become effective and efficient. In the end it provides increased income for farmers. There was an increase in Partner's revenue of Rp.372.000, - and Partner 2 of Rp. 618,000, - in September 2017 using a palm kernel collecting apparatus.